Acrylate latex as well as preparation method and application thereof
By controlling the average particle size and particle size span of latex particles in acrylic latex, a tight accumulation structure is formed, and the problem of insufficient performance of traditional hydropacitate compressive glue is solved. Waiting for performance improvement.
Patent Information
- Application Number
- CN202411505199.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional water-based acrylate pressure-sensitive adhesives have problems such as high surface energy, high temperature overflow, easy residual glue, whitening in soaking water, poor high and low temperature resistance, and high energy consumption of drying, making it difficult to meet the water resistance, moisture resistance and humidity resistance of daily chemical labels. etc. performance requirements.
By controlling the average particle size and particle size span of the latex particles in acrylic latex, the large particle -size latex is filled with small particle -size latex around it, forming a tight accumulation structure, improving the tightness of the glue film, thereby improving the water resistance of latex and chemical resistance of latex. Corrosion, humidity resistance and other properties.
The excellent water resistance, chemical resistance and humidity resistance of acrylate latex are achieved, and the preliminary adhesion and holding of the holding force are significantly improved, suitable for high -speed coating and large -scale production.
Smart Images

Figure BDA0005103748200000141 
Figure BDA0005103748200000151 
Figure BDA0005103748200000152
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pressure-sensitive adhesives, and in particular to an acrylic latex and a preparation method and application thereof. Background Art
[0002] Pressure-sensitive adhesive is an adhesive that is sensitive to pressure during the bonding process and can bond to the adherend under less pressure and within a very short contact time (commonly known as self-adhesive adhesive). It is one of the most widely used and produced adhesive varieties. Among them, polyacrylate pressure-sensitive adhesive is a homopolymer or copolymer of acrylic ester monomers. Due to its advantages such as good weather resistance, high transparency, simple production process, low cost, and wide bonding range, it is widely used in packaging technology, labels, tapes, protective films, medical supplies and other fields. With the introduction of the standard and regulations GB 33372-2020 "Limits of Volatile Organic Compounds in Adhesives", the trend of "oil-to-water" of acrylic pressure-sensitive adhesives has become more and more obvious. However, compared with solvent-based acrylic pressure-sensitive adhesives, traditional water-based acrylic pressure-sensitive adhesives have problems such as high surface energy, high-temperature overflow, easy residual glue, whitening after soaking in water, poor resistance to high and low temperatures, and high drying energy consumption that need to be solved urgently.
[0003] Patent CN113604176A discloses an acrylic pressure-sensitive adhesive emulsion and its application. By selecting a compound emulsifier, functional monomer, soft monomer and hard monomer, the coating speed is improved and the adhesive has low foaming, high solid content, strong peeling resistance, good dynamic wetting and leveling properties. The acrylic pressure-sensitive adhesive emulsion is combined with a curing agent to form an acrylic pressure-sensitive adhesive, which has high water resistance, a coating speed of up to 200m / min, a low coating temperature and high coating efficiency while ensuring high peeling force. However, due to the need for an external curing agent, the coating equipment has high requirements on stability and worker proficiency, and it is difficult to switch glue and convert production, which is not suitable for mass use.
[0004] Patent CN114891464A discloses a high initial viscosity and high temperature resistant water-based acrylic pressure-sensitive adhesive and its preparation method. The water-based acrylic pressure-sensitive adhesive with high initial viscosity is prepared by adjusting the type and proportion of the reactive acrylic ester monomer and adding a cross-linking agent. The groups in the emulsion form heat-reversible cross-linking hydrogen bonds at high temperatures through the NH bonds of the cross-linking agent and the polar groups in the acrylic ester monomer, such as oxygen in the carboxyl group, to enhance the cohesive strength of the acrylic adhesive layer, reduce residual glue, and achieve cross-linking control through heat-reversible hydrogen bonds, thereby improving the initial adhesion and peel strength of the acrylic emulsion. However, the pressure-sensitive adhesive prepared by the method has a lasting adhesion of only 1 to 2 hours and low cohesive strength. In actual use, it is easy to cause overflow and adhesion problems, which greatly affects the efficiency of die-cutting waste discharge.
[0005] In recent years, with the rapid development of social economy, label printing has become more colorful and widely penetrated into people's daily work and life. Among them, daily chemical products are important display commodities on the shelves of supermarkets and stores, so daily chemical labels are designed and printed around the demand orientation of "beautiful products, accurate labels, stable performance, unique technology, durable and reliable". Common daily chemical products in life include detergents, shampoo, shower gel, laundry detergent, facial cleanser and other products, the ingredients of which are mainly surfactants, acid-base regulators, preservatives, fragrances and other substances, and the ingredients are relatively complex. Daily chemical products are often placed in harsh environments such as humidity, hot water spraying, and soaking of daily chemical products, which causes conventional film labels made of acrylic latex pressure-sensitive adhesive to be prone to warping, bulging, and severe shedding on the bottle body, affecting the normal use of customers. Due to the unique sales and use environment of daily chemical products, daily chemical labels are not only required to have specific functions that meet the packaging effect, but also to have stable physical and chemical properties such as water resistance, moisture resistance, extrusion resistance, wear resistance, tear resistance, and corrosion resistance. Film labels that use PE (polyethylene film), PP (polypropylene film) and various mixtures of PP and PE as printing substrates have good protection and exquisite printing effects, and account for the largest proportion in the daily chemical field. Although there are many brands of film labels on the market, most of the daily chemical film labels that meet the characteristics of strong adhesion, water resistance, resistance to corrosion by daily chemical contents, and resistance to moisture and heat are mainly two-component solvent-based acrylic pressure-sensitive adhesives, while single-component water-based acrylic pressure-sensitive adhesive products that meet performance requirements and are suitable for high-speed coating are rarely reported. Summary of the invention
[0006] The object of the present invention is to provide an acrylate latex and a preparation method and application thereof. The acrylate latex provided by the present invention is a water-based latex and has excellent comprehensive properties.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The invention provides an acrylate latex, which comprises the following raw materials in parts by weight: 42-56 parts of soft monomers, 3-14 parts of hard monomers, 1-4 parts of functional monomers, 0.01-0.06 parts of molecular weight regulators, 1-3 parts of emulsifiers, 0.05-0.15 parts of buffers, 0.2-0.5 parts of initiators, 0.05-0.15 parts of oxidants, 0.05-0.15 parts of reducing agents, 0.3-0.7 parts of pH regulators, 0-0.6 parts of wetting agents, 0-0.1 parts of defoaming agents and 36-41 parts of water; the average particle size of latex particles in the acrylate latex is 400-750nm, and the particle size span of the latex particles in the acrylate latex is 0.5-1.2.
[0009] Preferably, the soft monomer includes one or more of butyl acrylate, isobutyl acrylate, ethyl acrylate, n-octyl acrylate and isooctyl acrylate.
[0010] Preferably, the hard monomer includes one or more of styrene, methyl acrylate, methyl methacrylate, vinyl versatate, vinyl acetate and acrylonitrile.
[0011] Preferably, the functional monomer includes one or more of acrylic acid, methacrylic acid, β-carboxyethyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, vinyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane.
[0012] Preferably, the molecular weight regulator includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoethanol and thioglycolic acid.
[0013] Preferably, the emulsifier includes one or more of an anionic emulsifier selected from the group consisting of disodium sulfosuccinate fatty alcohol ether monoester and ammonium allyloxy fatty alcohol polyoxyethylene ether sulfate.
[0014] Preferably, the initiator comprises one or more of potassium persulfate, ammonium persulfate and sodium persulfate.
[0015] Preferably, the wetting agent comprises one or more of acetylenediol ethoxylate and dioctyl sodium sulfosuccinate.
[0016] The present invention also provides a method for preparing the acrylic latex described in the above technical solution, comprising the following steps:
[0017] (1) mixing a part of the emulsifier, the first part of the water, the soft monomer, the hard monomer, all or part of the functional monomer and the molecular weight regulator, and then pre-emulsifying to obtain a pre-emulsified liquid;
[0018] (2) mixing a second portion of water, a buffer and a portion of the pre-emulsified liquid obtained in step (1) to obtain a bottom liquid;
[0019] (3) mixing the kettle bottom liquid obtained in step (2) with the third part of water and part of the initiator and performing a polymerization reaction to obtain a seed emulsion;
[0020] (4) mixing the seed emulsion obtained in step (3), the fourth portion of water, the remaining initiator, the remaining pre-emulsion obtained in step (1) and the remaining emulsifier for secondary nucleation, then adding an oxidant, a reducing agent and the remaining water for post-treatment, and then adding a pH adjuster to obtain an acrylate latex;
[0021] When part of the functional monomers are added in step (1), the remaining functional monomers are added in step (4);
[0022] When the acrylic emulsion includes a wetting agent and a defoaming agent, the wetting agent and the defoaming agent are added in step (4).
[0023] The present invention also provides the use of the acrylate latex described in the above technical solution or the acrylate latex prepared by the preparation method described in the above technical solution as a pressure-sensitive adhesive for daily chemical film labels.
[0024] The invention provides an acrylate latex, which comprises the following raw materials in parts by weight: 42-56 parts of soft monomers, 3-14 parts of hard monomers, 1-4 parts of functional monomers, 0.01-0.06 parts of molecular weight regulators, 1-3 parts of emulsifiers, 0.05-0.15 parts of buffers, 0.2-0.5 parts of initiators, 0.05-0.15 parts of oxidants, 0.05-0.15 parts of reducing agents, 0.3-0.7 parts of pH regulators, 0-0.6 parts of wetting agents, 0-0.1 parts of defoaming agents and 36-41 parts of water; the average particle size of latex particles in the acrylate latex is 400-750nm, and the particle size span of the latex particles in the acrylate latex is 0.5-1.2. The present invention controls the average particle size and particle size span of latex particles in acrylic latex, so that small particle size latex is filled around large particle size latex, and large particle size latex and small particle size latex form a tightly packed structure, reducing the gap between latex particles, improving the compactness of the film, so that the latex has excellent water resistance, chemical corrosion resistance, moisture and heat resistance and other properties, controls the composition of the latex and the amount of each component, and improves the initial adhesion and holding force of the latex. The results of the embodiment show that the initial adhesion of the acrylic latex provided by the present invention is above 10N / 25mm, the 90° peeling force is above 7N / 25mm, and the holding force is 240h without displacement, and has good water resistance, chemical corrosion resistance and moisture and heat resistance. DETAILED DESCRIPTION
[0025] The invention provides an acrylate latex, which comprises the following raw materials in parts by weight: 42-56 parts of soft monomers, 3-14 parts of hard monomers, 1-4 parts of functional monomers, 0.01-0.06 parts of molecular weight regulators, 1-3 parts of emulsifiers, 0.05-0.15 parts of buffers, 0.2-0.5 parts of initiators, 0.05-0.15 parts of oxidants, 0.05-0.15 parts of reducing agents, 0.3-0.7 parts of pH regulators, 0-0.6 parts of wetting agents, 0-0.1 parts of defoaming agents and 36-41 parts of water; the average particle size of latex particles in the acrylate latex is 400-750nm, and the particle size span of the latex particles in the acrylate latex is 0.5-1.2.
[0026] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.
[0027] In the present invention, the average particle size of the latex particles in the acrylic latex is 400-750nm, preferably 400-650nm, more preferably 450-600nm, and further preferably 500-550nm; the particle size span of the latex particles in the acrylic latex is 0.5-1.2, preferably 0.6-0.75, and further preferably 0.66-0.73. The present invention controls the average particle size and particle size span of the latex particles in the acrylic latex, so that the large particle size latex is filled with small particle size latex around, and the large particle size latex and the small particle size latex form a tightly packed structure, which reduces the gaps between the latex particles and improves the compactness of the film, thereby making the latex have excellent water resistance, chemical corrosion resistance, moisture and heat resistance and other properties.
[0028] The raw materials for preparing the acrylic latex of the present invention include 42 to 56 parts by weight, preferably 43 to 55 parts by weight of soft monomers. In the present invention, the soft monomers improve the flexibility of the film, and enhance the wettability and low-temperature performance of the adherend.
[0029] In the present invention, the soft monomer preferably includes one or more of butyl acrylate, isobutyl acrylate, ethyl acrylate, n-octyl acrylate and isooctyl acrylate, and more preferably includes isooctyl acrylate and butyl acrylate.
[0030] The raw materials for preparing the acrylic latex of the present invention include 3 to 14 parts of hard monomers, preferably 4 to 13 parts, based on 42 to 56 parts of soft monomers. In the present invention, the hard monomers increase the hardness of the film, enhance the cohesion, and improve the initial adhesion and lasting adhesion of the film.
[0031] In the present invention, the hard monomer preferably includes one or more of styrene, methyl acrylate, methyl methacrylate, versatate, vinyl acetate and acrylonitrile. In the present invention, the versatate has a highly branched aliphatic structure, and has a strong stereoprotective function for itself and adjacent monomers in the polymer chain, making the ester group on the polymer side chain difficult to hydrolyze, thereby further improving the water resistance and chemical resistance of the film. The present invention limits the amount and type of the hard monomer to the above range, which can further improve the hardness, initial adhesion and lasting adhesion of the film, and improve the water resistance, chemical resistance and other properties of the film.
[0032] The raw materials for preparing the acrylic latex of the present invention include 1 to 4 parts of functional monomers, preferably 2 to 3 parts, based on 42 to 56 parts of the mass of the soft monomer. In the present invention, the functional monomers introduce functional groups or crosslinking points on the acrylic ester molecular chain to improve the bonding force with the substrate, enhance the cohesive force, and thus improve the initial adhesion and the lasting adhesion.
[0033] In the present invention, the functional monomer preferably includes one or more of acrylic acid, methacrylic acid, β-carboxyethyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, vinyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane, and more preferably includes acrylic acid, hydroxyethyl methacrylate and vinyl trimethoxysilane. The present invention preferably introduces organosilicon functional monomers, introduces organosilicon molecules on polymer molecular segments, hydrolyzes silanol groups to form silanol groups during latex drying and film formation, and then condenses with each other to form a stable silicone structure (Si-O-Si), and the polymer segments form a three-dimensional network structure, which improves the molecular weight of the polymer, increases the density of the film, reduces the ability of the ester group to hydrolyze, and due to the presence of Si-O bonds, improves the flexibility of the polymer segments, can absorb excess energy when the stress in the label is not concentrated, prevents the label from warping and bulging, and further improves the water resistance and chemical resistance of the film. The present invention limits the amount and type of the functional monomers to the above range, which can further improve the water resistance, chemical resistance and other properties of the adhesive film.
[0034] Based on 42 to 56 parts of the soft monomer, the raw materials for preparing the acrylic latex of the present invention include 0.01 to 0.06 parts of molecular weight regulator, preferably 0.02 to 0.05 parts. In the present invention, the molecular weight regulator is used to adjust the size and distribution of molecular weight and improve the comprehensive properties of the latex, such as mechanical properties.
[0035] In the present invention, the molecular weight regulator preferably includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoethanol and thioglycolic acid. The present invention limits the amount and type of the molecular weight regulator to the above range, which can make the latex have a suitable molecular weight and distribution, and further improve the performance of the latex.
[0036] Based on the weight of the soft monomer being 42 to 56 parts, the raw materials for preparing the acrylic latex of the present invention include 1 to 3 parts of an emulsifier, preferably 1.5 to 2.5 parts. In the present invention, the emulsifier is a surfactant, which is composed of a polar hydrophilic group and a non-polar lipophilic group, and can form a substance such as micelles in water, thereby affecting the process of emulsion polymerization.
[0037] In the present invention, the emulsifier preferably includes one or more of a disodium salt of sulfosuccinic acid fatty alcohol ether monoester anionic emulsifier and an ammonium salt of allyloxy fatty alcohol polyoxyethylene ether sulfate polymerizable anionic emulsifier; more preferably includes a disodium salt of sulfosuccinic acid fatty alcohol ether monoester anionic emulsifier and an ammonium salt of allyloxy fatty alcohol polyoxyethylene ether sulfate polymerizable anionic emulsifier.
[0038] In the present invention, the disodium salt of fatty alcohol sulfosuccinate anionic emulsifier preferably includes one or more of Solvay AEROSOL EF800, Solvay AEROSOL EF810, Solvay AEROSOL A102, Solvay AEROSOLA-103, Double Bond DNS 330 and Solvay AEROSOL MA80.
[0039] In the present invention, the allyloxy fatty alcohol polyoxyethylene ether sulfate ammonium salt-based polymerizable anionic emulsifier preferably includes one or more of ADEKA SR10, Double Bond DNS 86 and Solvay REACTSURF 2490.
[0040] The present invention limits the amount of the emulsifier to the above range, and preferably uses an anionic emulsifier such as disodium salt of fatty alcohol ether monoester of sulfosuccinic acid and polymerizable anionic emulsifier such as ammonium salt of allyloxy fatty alcohol polyoxyethylene ether sulfate, so that the latex particles are multivariately distributed and have a suitable average particle size and particle size span. The small-sized latex particles fill the gaps of the large-sized latex particles, thereby increasing the space occupancy of the latex particles and maintaining a high degree of freedom of the latex particles. The large-sized latex particles have a small specific surface area, so the latex particles have a large surface area. The surface charge density of the particles is low, and the electrostatic repulsion of the double electric layer formed by the anionic emulsifier on the surface of the latex particles is small, which reduces the viscosity of the latex, thereby obtaining a high-solid and low-viscosity latex, which is suitable for high-speed coating and has good comprehensive performance; at the same time, adding a polymerizable emulsifier can improve the water resistance of the film. Since the polymerizable emulsifier is polymerized to the main chain of the acrylic resin, it will not migrate to the surface of the film as the water evaporates during the drying and film-forming process, reducing the gap channels between the latex particles, reducing the penetration of water molecules, and improving water resistance.
[0041] Based on 42 to 56 parts of the mass of the soft monomer, the raw materials for preparing the acrylic latex of the present invention include 0.05 to 0.15 parts of a buffer, preferably 0.07 to 0.12 parts. In the present invention, the buffer provides a suitable pH value for the reaction.
[0042] In the present invention, the buffer preferably includes one or more of sodium bicarbonate, ammonium bicarbonate, sodium carbonate, ammonium carbonate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, potassium bicarbonate and potassium carbonate. The present invention limits the amount and type of the buffer to the above range, so that the emulsion has a suitable pH value during synthesis, which is conducive to the formation of latex.
[0043] Based on 42 to 56 parts of the soft monomer, the raw materials for preparing the acrylic latex of the present invention include 0.2 to 0.5 parts of initiator, preferably 0.2 to 0.4 parts. In the present invention, the initiator is decomposed by heat in water to generate free radicals, which initiate free radical polymerization in the polymerization reaction to form acrylic latex.
[0044] In the present invention, the initiator preferably includes one or more of potassium persulfate, ammonium persulfate and sodium persulfate. The present invention limits the amount and type of the initiator to the above range, so that the polymerization reaction can be fully carried out.
[0045] Based on the weight of the soft monomer being 42 to 56 parts, the raw materials for preparing the acrylic latex of the present invention include 0.05 to 0.15 parts of an oxidant, preferably 0.05 to 0.12 parts. In the present invention, the oxidant and the reductant initiate the decomposition reaction of the residual monomers through an oxidation-reduction reaction, thereby reducing the residual small molecular monomer content in the latex in the later stage of the reaction, improving the performance of the latex while reducing the odor of the latex.
[0046] In the present invention, the oxidant is preferably tert-butyl hydroperoxide. The present invention limits the type and amount of the oxidant to the above range, which can further improve the latex performance and reduce the latex odor.
[0047] Based on the weight of the soft monomer being 42 to 56 parts, the raw materials for preparing the acrylic latex of the present invention include 0.05 to 0.15 parts of reducing agent, preferably 0.05 to 0.12 parts. In the present invention, the reducing agent and the oxidizing agent can initiate the decomposition of the residual monomers in the system through the redox reaction, reduce the residual small molecular monomer content in the latex in the later stage of the reaction, improve the performance of the latex and reduce the odor of the latex.
[0048] In the present invention, the reducing agent preferably includes one or more of ferrous sulfite, sodium nicotinsulfate, sodium formaldehyde sulfoxylate and sodium isoascorbate. The present invention limits the type and amount of the reducing agent to the above range, which can further improve the latex performance and reduce the latex odor.
[0049] Based on 42 to 56 parts by mass of the soft monomer, the raw materials for preparing the acrylic latex of the present invention include 0.3 to 0.7 parts of pH adjuster, preferably 0.3 to 0.6 parts. In the present invention, the pH adjustment is used to adjust the pH value of the latex and improve its storage stability.
[0050] In the present invention, the pH regulator preferably includes one or more of ammonia water, sodium hydroxide and triethanolamine. In the present invention, when the pH regulator is ammonia water, the mass concentration of the ammonia water is preferably 20-30%, more preferably 25%. The present invention limits the amount and type of the pH regulator to the above range, so that the latex can have a suitable pH value.
[0051] Based on the weight of the soft monomer being 42 to 56 parts, the raw materials for preparing the acrylic latex of the present invention include 0 to 0.6 parts of a wetting agent, preferably 0.1 to 0.6 parts. In the present invention, the wetting agent is a surfactant, contains hydrophilic and lipophilic groups, has an important influence on the coating property of the latex, can reduce the dynamic and static surface tension of the latex, and in the high-speed coating process, when the latex contacts the silicon-coated release paper, the lipophilic group adheres to the surface of the silicon-coated release paper, and the hydrophilic group extends outward into the glue, so that the glue forms a continuous phase on the surface of the silicon-coated release paper, ensuring that the latex film is uniform and complete, and preventing the problems of "heel", "missing coating", "fish eye" and the like on the adhesive surface of the self-adhesive sticker.
[0052] In the present invention, the wetting agent preferably includes one or more of acetylene glycol ethoxylate and dioctyl sodium sulfosuccinate, and more preferably includes one or more of Evonik Surfynol 420, Evonik Surfynol PSA336, Cytec OT-75 and BASF Hydropalat WE3475. The present invention limits the amount and type of the wetting agent to the above range, which can further improve the uniformity and integrity of the latex film.
[0053] Based on 42 to 56 parts by mass of the soft monomer, the raw materials for preparing the acrylic latex of the present invention include 0 to 0.1 parts of defoamer, preferably 0.01 to 0.1 parts. In the present invention, the defoamer can reduce the generation of bubbles during the coating process of latex production, avoiding problems such as "broken curtains" and "bubble points".
[0054] In the present invention, the defoamer preferably includes one or more of mineral oil and silicone modified defoamer, and more preferably includes one or more of Solvay DF300, Solvay Rhodoline DF 962-Z and BASF Foamaster 8034A. The present invention limits the amount and type of the defoamer to the above range, and can fully remove bubbles in the latex production and coating process.
[0055] Based on the mass of the soft monomer being 42 to 56 parts, the raw materials for preparing the acrylic latex of the present invention include 36 to 41 parts of water, preferably 37 to 40 parts. In the present invention, the water is preferably deionized water. The present invention limits the amount of water to the above range, which can make the latex have a suitable solid content and viscosity, and further improve the comprehensive performance of the latex.
[0056] In the present invention, the solid content of the acrylic latex is preferably 60-63%; the viscosity of the acrylic latex is preferably 250-600cps, the coating speed on the curtain equipment can reach 500m / min, and the coating can be continuously applied for more than 12h without stopping to clean the coating head, which greatly improves the production efficiency.
[0057] The present invention controls the composition of acrylic latex and the amount of each component, so that the average particle size of latex particles is 400-750nm, the particle size span is 0.5-1.2, small particle size latex is filled around large particle size latex, and large particle size latex and small particle size latex form a tightly packed structure, which reduces the gap between latex particles and improves the compactness of the film, so that the latex has excellent water resistance, chemical corrosion resistance, moisture and heat resistance and other properties, reduces the problems of "broken curtain", "leaky eyes" and "fish eyes" in the coating process, and improves the initial adhesion and lasting adhesion of the latex.
[0058] The present invention also provides a method for preparing the acrylic latex described in the above technical solution, comprising the following steps:
[0059] (1) mixing a part of the emulsifier, the first part of the water, the soft monomer, the hard monomer, all or part of the functional monomer and the molecular weight regulator, and then pre-emulsifying to obtain a pre-emulsified liquid;
[0060] (2) mixing a second portion of water, a buffer and a portion of the pre-emulsified liquid obtained in step (1) to obtain a bottom liquid;
[0061] (3) mixing the kettle bottom liquid obtained in step (2) with the third part of water and part of the initiator and performing a polymerization reaction to obtain a seed emulsion;
[0062] (4) mixing the seed emulsion obtained in step (3), the fourth portion of water, the remaining initiator, the remaining pre-emulsion obtained in step (1) and the remaining emulsifier for secondary nucleation, then adding an oxidant, a reducing agent and the remaining water for post-treatment, and then adding a pH adjuster to obtain an acrylate latex;
[0063] When part of the functional monomers are added in step (1), the remaining part of the functional monomers are added in step (4);
[0064] When the acrylic emulsion includes a wetting agent and a defoaming agent, the wetting agent and the defoaming agent are added in step (4).
[0065] The present invention mixes part of the emulsifier, the first part of water, the soft monomer, the hard monomer, all or part of the functional monomer and the molecular weight regulator, and then pre-emulsifies the mixture to obtain the pre-emulsified liquid.
[0066] In the present invention, the mass of the partial emulsifier is preferably 65-85% of the mass of the total emulsifier; the mass of the first portion of water is preferably 30-45% of the mass of the total water.
[0067] In the present invention, when some functional monomers are added, the mass of the some functional monomers is preferably 72-75% of the mass of the total functional monomers.
[0068] In the present invention, the pre-emulsification is preferably carried out under stirring conditions; the pre-emulsification temperature is preferably 10 to 35° C.; the pre-emulsification time is preferably 0.5 to 1 hour. The present invention has no particular limitation on the stirring rate, and the stirring rate well known to those skilled in the art can be used to fully emulsify the components.
[0069] After obtaining the pre-emulsion, the present invention mixes the second portion of water, a buffer and a portion of the pre-emulsion to obtain a kettle bottom liquid.
[0070] In the present invention, the mass of the second portion of water is preferably 40-55% of the mass of the total water; the mass of the portion of pre-emulsion is preferably 0.5-3% of the mass of the total emulsion.
[0071] In the present invention, the mixing of the second part of water, the buffer and part of the pre-emulsion is preferably as follows: the second part of water and the buffer are mixed, the temperature is raised to 50-60° C., and part of the pre-emulsion is added.
[0072] After obtaining the kettle bottom liquid, the present invention mixes the kettle bottom liquid with the third part of water and part of the initiator to carry out polymerization reaction to obtain the seed emulsion.
[0073] In the present invention, the mass of the third portion of water is preferably 1-5% of the total water mass; the mass of the portion of initiators is preferably 40-60% of the total initiators mass.
[0074] In the present invention, the mixing of the bottom liquid of the kettle and the third part of water and part of the initiator is preferably as follows: the third part of water and part of the initiator are mixed to obtain an initiator solution, the bottom liquid of the kettle is heated to 84-86° C., and the initiator solution is added under stirring.
[0075] In the present invention, the polymerization reaction temperature is preferably 84-86° C.; the polymerization reaction time is preferably 20-40 min.
[0076] After obtaining the seed emulsion, the present invention mixes the seed emulsion, the fourth part of water, the remaining initiator, the remaining pre-emulsion and the remaining emulsifier for secondary nucleation, then adds an oxidant, a reducing agent and the remaining water for post-treatment, and then adds a pH regulator to obtain an acrylate latex.
[0077] In the present invention, the mass of the fourth portion of water is preferably 1-10% of the mass of the total water.
[0078] In the present invention, the seed emulsion, the fourth part of water, the remaining initiator, the remaining pre-emulsion and the remaining emulsifier are preferably mixed as follows: the fourth part of water and the remaining initiator are mixed to obtain an initiator solution, and the initiator solution and the remaining pre-emulsion are dripped into the seed emulsion at 84-86° C. and under stirring; the dripping time is preferably 210-270 min; when the dripping reaches 95-175 min, the remaining emulsifier is quickly added, and the initiator solution and the remaining pre-emulsion are reacted for 50-70 min after the dripping is completed.
[0079] The present invention has no particular limitation on the adding rate of the rapid addition of the remaining emulsifier, and the remaining emulsifier can be added in a relatively short time.
[0080] In the present invention, when a part of the emulsifier, the first part of water, the soft monomer, the hard monomer, a part of the functional monomer and the molecular weight regulator are mixed and then pre-emulsified, the remaining functional monomer is added when the seed emulsion, the fourth part of water, the remaining initiator, the remaining pre-emulsion and the remaining emulsifier are mixed.
[0081] In the present invention, when the remaining pre-emulsion liquid is added dropwise to 30-40% of the total mass of the remaining pre-emulsion liquid, the remaining functional monomer is mixed with the pre-emulsion liquid and then added dropwise.
[0082] In the present invention, the reducing agent and the oxidizing agent are preferably added in the form of a reducing agent solution and an oxidizing agent solution.
[0083] In the present invention, the reducing agent and the oxidizing agent are preferably mixed with part of the water respectively to obtain the reducing agent solution and the oxidizing agent solution.
[0084] In the present invention, the mass of the part of water mixed with the reducing agent is preferably 1-5% of the total water mass; the mass of the part of water mixed with the oxidizing agent is preferably 1-5% of the total water mass.
[0085] In the present invention, the temperature when adding the oxidant solution and the reducing agent solution is preferably 60-75°C.
[0086] In the present invention, the oxidant solution and the reducing agent solution are preferably added dropwise simultaneously; the time for the addition is preferably 30 to 60 minutes.
[0087] In the present invention, the temperature when the pH adjuster is added is preferably <45°C.
[0088] In the present invention, after adding the pH adjuster, the pH value of the system is preferably 7-8.
[0089] In the present invention, when the acrylic emulsion includes a wetting agent and a defoaming agent, the wetting agent and the defoaming agent are preferably added sequentially after the pH adjuster is added.
[0090] After adding the wetting agent and the defoaming agent, the present invention preferably disperses and filters the system after adding the wetting agent and the defoaming agent in sequence to obtain the acrylic latex.
[0091] The present invention has no special limitation on the dispersing operation, and the wetting agent and the defoaming agent can be evenly dispersed using a dispersing technical solution well known to those skilled in the art.
[0092] In the present invention, the filtration is preferably performed using a 300-mesh nylon filter bag and a diaphragm pump for automatic filtration.
[0093] The method for preparing the acrylic latex of the present invention preferably comprises the following steps:
[0094] (1) 65-85 wt% of an emulsifier, 30-45 wt% of water, a soft monomer, a hard monomer, all or 72-75 wt% of a functional monomer and a molecular weight regulator are mixed and stirred for 0.5-1 h to obtain a pre-emulsion;
[0095] (2) mixing 40-55 wt % of water and a buffer, heating the mixture to 50-60° C., and adding 0.5-3 wt % of the pre-emulsified liquid obtained in step (1) to obtain a bottom liquid;
[0096] (3) heating the kettle bottom liquid obtained in step (2) to 84-86° C., adding 40-60 wt % of an initiator dissolved in 1-5 wt % of water to the kettle bottom liquid under stirring, and performing a polymerization reaction for 20-40 min to obtain a seed emulsion;
[0097] (4) adding the remaining initiator solution and the remaining pre-emulsion dissolved in 1-10 wt% water to the seed emulsion obtained in step (3) at 84-86° C. with stirring for 210-270 min. When the addition reaches 95-175 min, the remaining emulsifier is quickly added for secondary nucleation. After the addition is completed, the mixture is kept warm for 50-70 min, cooled to 60-75° C., the oxidant and the reductant are dissolved in 1-5 wt% water respectively, and the mixture is added simultaneously for 30-60 min. The mixture is cooled to below 45° C., a pH adjuster is added to a pH value of 7-8, a wetting agent and a defoaming agent are added, and the mixture is filtered after complete dispersion to obtain an acrylic latex.
[0098] When 72-75 wt % of the functional monomer is added in step (1), the step (4) comprises: adding the remaining initiator solution and the remaining pre-emulsion dissolved in 1-5 wt % of water to the seed emulsion obtained in step (3) under stirring at 84-86° C. for 210-270 min; when the addition reaches 95-175 min, adding the remaining emulsifier for secondary nucleation; when the remaining pre-emulsion is added to 30-40% of the total mass of the remaining pre-emulsion, mixing the remaining functional monomer with the pre-emulsion and continuing to add the pre-emulsion; keeping the temperature for 50-70 min after the addition is completed, cooling to 60-75° C., dissolving the oxidant and the reductant in 1-5 wt % of water respectively, and adding the pre-emulsion simultaneously for 30-60 min; cooling to below 45° C., adding a pH adjuster until the pH value is 7-8, adding a wetting agent and a defoaming agent, filtering after complete dispersion, and obtaining an acrylic latex.
[0099] The present invention adds an emulsifier at the later stage of the reaction to perform secondary nucleation, so that the latex particles are multivariately distributed and the comprehensive performance of the latex is improved.
[0100] The present invention also provides the use of the acrylate latex described in the above technical solution or the acrylate latex prepared by the preparation method described in the above technical solution as a pressure-sensitive adhesive for daily chemical film labels.
[0101] The present invention has no special limitation on the operation of the application, and the technical solutions of the application well known to those skilled in the art may be adopted.
[0102] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0103] Example 1
[0104] An acrylic latex is prepared from the following raw materials, measured by weight: 53.161 parts of soft monomers (including 24.950 parts of isooctyl acrylate and 28.211 parts of butyl acrylate, both from Shanghai Zhanyun Chemical Co., Ltd.), 5.954 parts of hard monomers methyl methacrylate (including 0.709 parts of acrylic acid and 0.907 parts of hydroxyethyl methacrylate, both from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (including 0.567 parts of REACTSURF 2490 polymerizable anionic emulsifier, DNS 330 anionic emulsifier 1.248 parts, MA80 anionic emulsifier 0.340 parts), buffer sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.284 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidant tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH adjuster (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.425 parts and deionized water 36.150 parts;
[0105] The preparation method of the acrylic latex is:
[0106] (1) 0.567 parts of REACTSURF 2490 polymerizable anionic emulsifier, 1.248 parts of DNS 330 anionic emulsifier (the total mass of REACTSURF 2490 polymerizable anionic emulsifier and DNS330 anionic emulsifier is 84.2% of the total mass of the emulsifier), 15.5445 parts of deionized water (43% of the total water mass), 24.950 parts of isooctyl acrylate (EHA), 28.211 parts of butyl acrylate (BA), 5.954 parts of methyl methacrylate (MMA), 0.709 parts of acrylic acid (AA), 0.907 parts of hydroxyethyl methacrylate (HEMA), and 0.028 parts of n-dodecyl mercaptan (NDM) are sequentially added into an emulsifier, stirred and dispersed for 0.5 hours to prepare a pre-emulsion;
[0107] (2) adding 14.8215 parts of deionized water (41% of the total water mass) and 0.085 parts of sodium bicarbonate into a reaction kettle, heating the kettle to 55° C., and adding 1.5 wt % of the pre-emulsified liquid to prepare a kettle bottom liquid;
[0108] (3) The bottom liquid of the kettle was further heated to 85° C., and 0.1562 parts of initiator (55% of the total initiator mass) dissolved in 1.446 parts of deionized water (4% of the total water mass) was added to the bottom liquid of the kettle under stirring, and the reaction was carried out for 0.5 h to obtain a seed emulsion;
[0109] (4) Under stirring conditions, 0.1278 parts of an initiator solution dissolved in 2.892 parts of deionized water (8% of the total water mass) and the remaining pre-emulsion were uniformly added dropwise to the reactor, and the addition time was controlled at 240 minutes. When the pre-emulsion was added dropwise to 132 minutes, 0.340 parts of MA80 anionic emulsifier was quickly added to perform secondary nucleation. After the initiator solution and the pre-emulsion were added dropwise, the temperature was kept for 1 hour; the temperature was lowered to 70°C, 0.071 parts of tert-butyl hydroperoxide and 0.071 parts of sodium bisulfite were dissolved in 0.723 parts of deionized water (2% of the total water mass), respectively, and the addition time was 1 hour; the temperature was lowered to below 45°C, 0.425 parts of ammonia water (mass concentration 25%) were added to adjust the pH value to 7.5, and the acrylic latex pressure-sensitive adhesive was obtained by filtration.
[0110] Embodiments 2 to 10
[0111] The amounts of the components used in Examples 2 to 10 and the amount of the pre-emulsion added in step (2) are shown in Table 1, and the other parameters are the same as in Example 1.
[0112] Table 1 The dosage of each component in Examples 1 to 10
[0113]
[0114]
[0115] The average particle size, particle size span and water resistance of the acrylic latex prepared in Examples 1 to 10 were tested. The results are shown in Table 2.
[0116] Particle size test: Bettersize 2600 laser particle size distribution analyzer (wet method) was used to test the latex particle size.
[0117] Quick water resistance test: press the latex at 20g / m 2 The dry weight was coated on a 50 μm transparent BOPP film, placed in a 90°C oven for 8 minutes, and the adhesive surface of the surface material was laminated to a 61 g / m 2 The white release paper is coated with silicon and balanced under standard environment for 72 hours. After tearing off the label backing paper, soak it in 50℃ water and observe the color change for 5 minutes, 30 minutes and 2 hours respectively. The evaluation level is divided into 1 to 5 levels, with 1 being the worst water resistance and 5 being the best water resistance (Note: 1: white opaque; 2: bluish white semi-transparent; 3: blue transparent; 4: slightly blue transparent; 5: no color change and transparent).
[0118] Table 2 Average particle size, particle size span and water resistance of acrylic latex prepared in Examples 1 to 10
[0119]
[0120]
[0121] As shown in Table 2, the larger the average particle size of the latex particles and the wider the particle size distribution (greater than 550nm, the particle size span is greater than 0.730), the latex particles do not show the best tight packing when drying and forming the film, the gaps between the latex particles are of different sizes, the film has strong water absorption and poor water resistance. And too large a particle size will lead to a decrease in the storage stability and mechanical stability of the latex, an increase in the amount of slag discharge, and affect normal use. However, when the average particle size of the latex particles is smaller and the particle size distribution is narrower (for example, less than 500nm, the particle size span is less than 0.660), the viscosity of the latex is higher, and the fluidity under high-speed shear is poor, resulting in a decrease in the density of the film and affecting the water resistance. When the average particle size of the latex particles is between 500 and 550nm and the particle size span is between 0.660 and 0.730, the latex particles are most densely packed, and the water resistance of the film shows a better effect. At the same time, by introducing a polymerizable emulsifier, the water resistance of the film can be improved. Since the polymerizable emulsifier is polymerized on the main chain of the acrylic resin, it will not migrate to the surface of the film as the water evaporates during the drying and film-forming process, thereby reducing the gap channels between the latex particles, reducing the penetration of water molecules, and improving water resistance.
[0122] Embodiment 11
[0123] An acrylic latex is prepared from the following raw materials, measured by weight: 48.65 parts of soft monomers (including 29.699 parts of isooctyl acrylate and 18.951 parts of butyl acrylate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 9.419 parts of hard monomers (including 3.762 parts of methyl methacrylate and 5.657 parts of vinyl ester carbonate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.517 parts of functional monomers (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate and 0.905 parts of vinyl trimethoxysilane, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH regulator (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0124] The preparation method of the acrylic latex is:
[0125] (1) 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier, 0.848 parts of DNS 330 anionic emulsifier (the total mass of REACTSURF 2490 polymerizable anionic emulsifier and DNS 330 anionic emulsifier is 78% of the total mass of the emulsifier), 15.5058 parts of deionized water (43% of the total mass of water), 29.699 parts of isooctyl acrylate (EHA), 18.951 parts of butyl acrylate (BA), 3.762 parts of methyl methacrylate (MMA), 0.707 parts of acrylic acid (AA), 0.905 parts of hydroxyethyl methacrylate (HEMA), 5.657 parts of versatate vinyl carbonate (VV-10), 0.905 parts of vinyl trimethoxysilane (A-171), and 0.028 parts of n-dodecyl mercaptan (NDM) are sequentially added into an emulsifier, stirred and dispersed for 0.5 hours to prepare a pre-emulsion;
[0126] (2) adding 14.7846 parts of deionized water (41% of the total water mass) and 0.085 parts of sodium bicarbonate into a reaction kettle, heating the kettle to 55° C., and adding 1.5 wt % of the pre-emulsified liquid to prepare a kettle bottom liquid;
[0127] (3) The bottom liquid of the kettle was further heated to 85° C., and 0.15565 parts of initiator (55% of the total initiator mass) dissolved in 1.4424 parts of deionized water (4% of the total water mass) was added to the bottom liquid of the kettle under stirring. The reaction time was 0.5 h to obtain a seed emulsion.
[0128] (4) At 85°C, under stirring, 0.12735 parts of an initiator solution dissolved in 2.8848 parts of deionized water (8% of the total water mass) and the remaining pre-emulsion were uniformly added dropwise to the reactor. The addition time was controlled at 4 hours. When the pre-emulsion had been added for 132 minutes, 0.453 parts of MA80 anionic emulsifier was quickly added to perform secondary nucleation. After the initiator solution and pre-emulsion were added dropwise, the temperature was kept for 1 hour. The temperature was lowered to 7 At 0°C, 0.071 parts of tert-butyl hydroperoxide and 0.071 parts of sodium bisulfite were dissolved in 0.7217 parts of deionized water (2% of the total water mass), and the mixture was added dropwise simultaneously. The addition time was controlled at 1 h. The mixture was cooled to below 45°C, and 0.424 parts of ammonia water (mass concentration was 25%) were added to adjust the pH value to 7.5. 0.283 parts of wetting agent PSA336 and 0.028 parts of defoaming agent Foamaster 8034A were added, and the mixture was filtered after complete dispersion to obtain an acrylic latex pressure-sensitive adhesive.
[0129] Example 12
[0130] An acrylic latex is prepared from the following raw materials, measured by weight: 46.669 parts of soft monomers (including 33.941 parts of isooctyl acrylate and 12.728 parts of butyl acrylate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 11.398 parts of hard monomers (including 2.913 parts of methyl methacrylate and 8.485 parts of vinyl ester carbonate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.517 parts of functional monomers (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate and 0.905 parts of vinyl trimethoxysilane, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH regulator (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0131] The preparation method of the acrylic latex is the same as that of Example 11.
[0132] Embodiment 13
[0133] An acrylic latex is prepared from the following raw materials, measured by weight: 46.755 parts of soft monomers (including 38.552 parts of isooctyl acrylate and 8.203 parts of butyl acrylate, both from Shanghai Zhanyun Chemical Co., Ltd.), 11.314 parts of hard monomers (including 5.657 parts of methyl methacrylate and 5.657 parts of vinyl ester carbonate, both from Shanghai Zhanyun Chemical Co., Ltd.), 2.517 parts of functional monomers (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate and 0.905 parts of vinyl trimethoxysilane, both from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH regulator (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0134] The preparation method of the acrylic latex is the same as that of Example 11.
[0135] Embodiment 14
[0136] An acrylic latex is prepared from the following raw materials, measured by weight: 48.65 parts of soft monomers (including 29.699 parts of isooctyl acrylate and 18.951 parts of butyl acrylate, Shanghai Zhanyun Chemical Co., Ltd.), 9.419 parts of hard monomers (including 3.762 parts of methyl methacrylate and 5.657 parts of vinyl ester carbonate, Shanghai Zhanyun Chemical Co., Ltd.), 2.517 parts of functional monomers (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate and 0.905 parts of vinyl trimethoxysilane, Shanghai Zhanyun Chemical Co., Ltd.), 0.042 parts of molecular weight regulator n-dodecyl mercaptan (Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier, DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH adjuster (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0137] The preparation method of the acrylic latex is the same as that of Example 11.
[0138] Embodiment 15
[0139] An acrylic latex is prepared from the following raw materials, measured by weight: 48.65 parts of soft monomers (including 29.699 parts of isooctyl acrylate and 18.951 parts of butyl acrylate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 9.419 parts of hard monomers (including 3.762 parts of methyl methacrylate and 5.657 parts of vinyl ester carbonate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.814 parts of functional monomers (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate and 1.202 parts of vinyl trimethoxysilane, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH adjuster (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0140] The preparation method of the acrylic latex is the same as that of Example 11.
[0141] Example 16
[0142] An acrylic latex is prepared from the following raw materials, measured by weight: 48.65 parts of soft monomers (including 29.699 parts of isooctyl acrylate and 18.951 parts of butyl acrylate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 9.419 parts of hard monomers (including 3.762 parts of methyl methacrylate and 5.657 parts of vinyl ester carbonate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.206 parts of functional monomers (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate and 0.594 parts of vinyl trimethoxysilane, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH regulator (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0143] The preparation method of the acrylic latex is:
[0144] (1) 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier, 0.848 parts of DNS 330 anionic emulsifier (the total mass of REACTSURF 2490 polymerizable anionic emulsifier and DNS 330 anionic emulsifier is 78% of the total mass of emulsifier), 15.5058 parts of deionized water (43% of the total mass of water), 29.699 parts of isooctyl acrylate (EHA), 18.951 parts of butyl acrylate (BA), 3.762 parts of methyl methacrylate (MMA), 0.707 parts of acrylic acid (AA), 0.905 parts of hydroxyethyl methacrylate (HEMA) (the total mass of acrylic acid and hydroxyethyl methacrylate is 73% of the total mass of functional monomers), 5.657 parts of versatate (VV-10), and 0.028 parts of n-dodecyl mercaptan (NDM) are sequentially added into an emulsifier, stirred and dispersed for 0.5 hours to prepare a pre-emulsion;
[0145] (2) adding 14.7846 parts of deionized water (41% of the total water mass) and 0.085 parts of sodium bicarbonate into a reaction kettle, heating the kettle to 55° C., and adding 1.5 wt % of the pre-emulsified liquid to prepare a kettle bottom liquid;
[0146] (3) The bottom liquid of the kettle was further heated to 85° C., and 0.15565 parts of initiator (55% of the total initiator mass) dissolved in 1.4424 parts of deionized water (4% of the total water mass) was added to the bottom liquid of the kettle under stirring. The reaction time was 0.5 h to obtain a seed emulsion.
[0147] (4) At 85° C., under stirring conditions, 0.12735 parts of an initiator solution dissolved in 2.8848 parts of deionized water (8% of the total water mass) and the remaining pre-emulsion were uniformly added dropwise to the reactor, and the addition time was controlled at 4 hours. When the pre-emulsion had been added dropwise for 132 minutes, 0.453 parts of MA80 anionic emulsifier was quickly added for secondary nucleation. When the pre-emulsion was added dropwise to 35% of the total mass of the remaining pre-emulsion, 0.594 parts of vinyl trimethoxy silane was added to the remaining pre-emulsion at one time. Then continue to add dropwise, keep warm for 1 hour after the initiator solution and the pre-emulsion are added; cool to 70°C, dissolve 0.071 parts of tert-butyl hydroperoxide and 0.071 parts of sodium bisulfite in 0.7212 parts of deionized water (2% of the total water mass), respectively, and add dropwise simultaneously, the dropping time is controlled within 1 hour, cool to below 45°C, add 0.424 parts of ammonia water (mass concentration is 25%) to adjust the pH value to 7.5; add 0.283 parts of wetting agent PSA336 and 0.028 parts of defoaming agent Foamaster 8034A, and filter after complete dispersion to obtain an acrylic latex pressure-sensitive adhesive.
[0148] Embodiment 17
[0149] An acrylic latex is prepared from the following raw materials, measured by weight: 48.65 parts of soft monomers (including 29.699 parts of isooctyl acrylate and 18.951 parts of butyl acrylate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 9.419 parts of hard monomers (including 3.762 parts of methyl methacrylate and 5.657 parts of vinyl ester carbonate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.602 parts of functional monomers (including 0.566 parts of acrylic acid, 1.131 parts of hydroxyethyl methacrylate and 0.905 parts of vinyl trimethoxysilane, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH adjuster (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0150] The preparation method of the acrylic latex is the same as that of Example 11.
[0151] Embodiment 18
[0152] An acrylic latex is prepared from the following raw materials, measured by weight: 52.128 parts of soft monomer (including 24.692 parts of isooctyl acrylate and 27.436 parts of butyl acrylate, Shanghai Zhanyun Chemical Co., Ltd.), 5.940 parts of hard monomer methyl methacrylate (Shanghai Zhanyun Chemical Co., Ltd.), 2.517 parts of functional monomer (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate, and 0.905 parts of vinyl trimethoxysilane, Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifier (including 0.778 parts of REACTSURF2490 polymerizable anionic emulsifier, DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH regulator (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0153] The preparation method of the acrylic latex is the same as that of Example 11.
[0154] Embodiment 19
[0155] An acrylic latex is prepared from the following raw materials, measured by weight: 48.65 parts of soft monomers (including 29.699 parts of isooctyl acrylate and 18.951 parts of butyl acrylate, both from Shanghai Zhanyun Chemical Co., Ltd.), 9.419 parts of hard monomers (including 3.762 parts of methyl methacrylate and 5.657 parts of tert-butyl carbonate, both from Shanghai Zhanyun Chemical Co., Ltd.), 1.612 parts of functional monomers (including 0.707 parts of acrylic acid and 0.905 parts of hydroxyethyl methacrylate, both from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (both from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffer sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidant tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH adjuster (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster8034A 0.028 parts and deionized water 36.06 parts;
[0156] The preparation method of the acrylic latex is the same as that of Example 11.
[0157] Embodiment 20
[0158] An acrylic latex is prepared from the following raw materials, measured by weight: 48.65 parts of soft monomers (including 29.699 parts of isooctyl acrylate and 18.951 parts of butyl acrylate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 9.419 parts of hard monomers (including 3.762 parts of methyl methacrylate and 5.657 parts of vinyl ester carbonate, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.517 parts of functional monomers (including 0.707 parts of acrylic acid, 0.905 parts of hydroxyethyl methacrylate and 0.905 parts of vinyl trimethoxysilane, both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (both of which are from Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifiers (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier and 0.778 parts of DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH adjuster (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent OT75 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0159] The preparation method of the acrylic latex is the same as that of Example 11.
[0160] Embodiment 21
[0161] An acrylic latex is prepared from the following raw materials, measured by weight: 52.468 parts of soft monomer (including 25.598 parts of isooctyl acrylate and 26.870 parts of butyl acrylate, Shanghai Zhanyun Chemical Co., Ltd.), 6.505 parts of hard monomer methyl methacrylate (Shanghai Zhanyun Chemical Co., Ltd.), 1.612 parts of functional monomer (including 0.707 parts of acrylic acid and 0.905 parts of hydroxyethyl methacrylate, Shanghai Zhanyun Chemical Co., Ltd.), 0.028 parts of molecular weight regulator n-dodecyl mercaptan (Shanghai Zhanyun Chemical Co., Ltd.), 2.079 parts of emulsifier (including 0.778 parts of REACTSURF 2490 polymerizable anionic emulsifier, DNS 330 anionic emulsifier 0.848 parts, MA80 anionic emulsifier 0.453 parts), buffering agent sodium bicarbonate 0.085 parts (Shanghai Zhanyun Chemical Co., Ltd.), initiator ammonium persulfate 0.283 parts (Shanghai Zhanyun Chemical Co., Ltd.), oxidizing agent tert-butyl hydroperoxide 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), reducing agent sodium bisulfite 0.071 parts (Shanghai Zhanyun Chemical Co., Ltd.), pH regulator (25% mass concentration of ammonia water, Shanghai Zhanyun Chemical Co., Ltd.) 0.424 parts, wetting agent PSA336 0.283 parts, defoaming agent Foamaster 8034A 0.028 parts and deionized water 36.06 parts;
[0162] The preparation method of the acrylic latex is the same as that of Example 11.
[0163] The samples of Examples 11 to 21 were coated on 61 g / m 2 White release paper with silicone coating, glue coating amount is 20g / m 2 After coating, put it into a 90℃ oven for 8 minutes and take it out. Then transfer the adhesive film to the corona surface of the 82μm bright white PE film surface material. Finally, stick the adhesive surface of the surface material to the 61g / m 2 The silicon-coated surface of the white release paper was equilibrated under standard conditions for 72 hours before testing. The results are shown in Table 3.
[0164] Initial adhesion: Tested according to the "Ring Initial Adhesion Test" FTM9.
[0165] Peel force: Tested according to "90° Peel Force Test" FTM2.
[0166] Adhesion: Tested according to "Adhesion Test on Standard Panel" FTM8.
[0167] Application test: Cut the self-adhesive label into 5mm*10mm size, stick the label on a 1-liter cylindrical HDPE bottle, balance it under standard environment for 24 hours, and then conduct various resistance tests.
[0168] Water resistance test: Soak the labeled bottle in water, soaking more than 2 / 3 of the label, and place it at room temperature for 7 days to observe whether the label is warping, bubbling, or falling off. Test quantity: 5 labels; if there is no warping, bubbling, or falling off, it is passed, otherwise it is failed.
[0169] Contents corrosion resistance test: Soak the labeled bottles in commercially available laundry detergent, shower gel, shampoo, dishwashing liquid, and conditioner, with the immersion exceeding 2 / 3 of the label, and place them at room temperature for 7 days to observe whether the labels are warping, bubbling, or falling off. Test quantity: 5 labels for each of the above 5 types of daily chemicals; if the labels do not warp, bubble, or fall off, they pass; otherwise, they fail.
[0170] Heat and humidity resistance test: Soak the labeled bottles in commercial laundry detergent, shower gel, shampoo, dishwashing liquid, and conditioner, with the immersion exceeding 2 / 3 of the label, and place them in a 50℃, 65%RH environment for 7 days to observe whether the labels are warping, bubbling, or falling off. Test quantity: 5 labels for each of the above 5 types of daily chemicals; if the labels do not warp, bubble, or fall off, they pass; otherwise, they fail.
[0171] Table 3 Average particle size, particle size span, initial adhesion, 90° peel strength, sustained adhesion, water resistance test, content corrosion resistance test and moisture and heat resistance test results of acrylic latex in Examples 11 to 21
[0172]
[0173]
[0174] As can be seen from Table 3, the acrylic latex prepared by the present invention is cleverly designed for the size and distribution of latex particles, combined with the water-resistant monomer tert-butyl vinyl carbonate and the functional monomer vinyl trimethoxysilane, and the pressure-sensitive adhesive has an initial ring adhesion greater than 10N / 25mm, a 90° peeling force greater than 6.5N / 25mm in 20 minutes, and a holding force greater than 240h. It has good comprehensive mechanical properties, and the coating speed on the curtain equipment can reach 500m / min, and the coating can be continuously coated for more than 12h without stopping to clean the coating head, which greatly improves production efficiency and reduces unplanned downtime. At the same time, the prepared acrylic latex has excellent water resistance, resistance to corrosion by daily chemical content, and resistance to moisture and heat, and can meet most application scenarios of film labels for daily chemical products.
[0175] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An acrylic latex, comprising the following raw materials, by weight: 42-56 parts of soft monomers, 3-14 parts of hard monomers, 1-4 parts of functional monomers, 0.01-0.06 parts of molecular weight regulators, 1-3 parts of emulsifiers, 0.05-0.15 parts of buffers, 0.2-0.5 parts of initiators, 0.05-0.15 parts of oxidants, 0.05-0.15 parts of reducing agents, 0.3-0.7 parts of pH regulators, 0-0.6 parts of wetting agents, 0-0.1 parts of defoaming agents and 36-41 parts of water; the average particle size of the latex particles in the acrylic latex is 400-750 nm, and the particle size span of the latex particles in the acrylic latex is 0.5-1.
2.
2. The acrylic latex according to claim 1, characterized in that The soft monomer includes one or more of butyl acrylate, isobutyl acrylate, ethyl acrylate, n-octyl acrylate and isooctyl acrylate.
3. The acrylic latex according to claim 1, characterized in that The hard monomer includes one or more of styrene, methyl acrylate, methyl methacrylate, vinyl versatate, vinyl acetate and acrylonitrile.
4. The acrylic latex according to claim 1, characterized in that The functional monomers include one or more of acrylic acid, methacrylic acid, β-carboxyethyl acrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, vinyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane.
5. The acrylic latex according to claim 1, characterized in that: The molecular weight regulator includes one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, mercaptoethanol and thioglycolic acid.
6. The acrylic latex according to claim 1, characterized in that: The emulsifier includes one or more of a disodium salt of sulfosuccinic acid fatty alcohol ether monoester anionic emulsifier and an ammonium salt of allyloxy fatty alcohol polyoxyethylene ether sulfate polymerizable anionic emulsifier.
7. The acrylic latex according to claim 1, characterized in that: The initiator includes one or more of potassium persulfate, ammonium persulfate and sodium persulfate.
8. The acrylic latex according to claim 1, characterized in that The wetting agent includes one or more of acetylenediol ethoxylate and dioctyl sodium sulfosuccinate.
9. The method for preparing the acrylic latex according to any one of claims 1 to 8, comprising the following steps: (1) mixing a part of the emulsifier, the first part of the water, the soft monomer, the hard monomer, all or part of the functional monomer and the molecular weight regulator, and then pre-emulsifying to obtain a pre-emulsified liquid; (2) mixing a second portion of water, a buffer and a portion of the pre-emulsified liquid obtained in step (1) to obtain a bottom liquid; (3) mixing the kettle bottom liquid obtained in step (2) with the third part of water and part of the initiator and performing a polymerization reaction to obtain a seed emulsion; (4) mixing the seed emulsion obtained in step (3), the fourth portion of water, the remaining initiator, the remaining pre-emulsion obtained in step (1) and the remaining emulsifier for secondary nucleation, then adding an oxidant, a reducing agent and the remaining water for post-treatment, and then adding a pH adjuster to obtain an acrylate latex; When part of the functional monomers are added in step (1), the remaining functional monomers are added in step (4); When the acrylic emulsion includes a wetting agent and a defoaming agent, the wetting agent and the defoaming agent are added in step (4).
10. Use of the acrylate latex according to any one of claims 1 to 8 or the acrylate latex prepared by the preparation method according to claim 9 as a pressure-sensitive adhesive for daily chemical film labels.
Citation Information
Patent Citations
Acrylic pressure-sensitive adhesive emulsion and application thereof
CN113604176A